Experimental Investigation and Numerical Analyses on Cyclic Behavior of the Prefabricated Concrete Frame Infilled with CFS-CLPM Composite Walls - Peifang Hu; Yong Liu; Jingfeng Wang; Wanqian Wang; Guangdong Pan (Buildings, 2022)
A novel CFS composite wall filled with cement-based lightweight polymer material (CFS-CLPM composite wall) has been proposed and proven to have excellent architectural and mechanical performance. To promote its application in prefabricated concrete (PC) frame structures, two full-scale specimens were designed and tested under cyclic loading to investigate the failure mode, hysteretic response and energy dissipation of the PC frame infilled with the CFS-CLPM composite wall. The experimental results indicated that CFS-CLPM composite walls can significantly improve the lateral behavior of the PC frame in terms of load capacity, elastic stiffness and energy dissipation capacity, while slightly reducing its ductility because of the infill-frame interaction. Subsequently, finite element (FE) analyses for the PC frame infilled with CFS-CLPM composite walls were developed and verified against the experimental results. The force-transferring mechanisms between the PC frame and the CFS-CLPM composite walls were revealed by analyzing the stress distributions. The parametric analyses demonstrated that the influential parameters for lateral resistances of the PC frame structure infilled with CFS-CLPM composite walls were the strength of CLPM, the span-to-height ratio and the thickness of CFS-CLPM composite walls. Finally, a formula considering the mechanical contribution of the CFS-CLPM composite wall was proposed to predict the elastic lateral stiffness of the structures. The results of this study could provide a basis for the application of CFS-CLPM composite walls in PC frame structures.